Environmental and Health impact of Agrochemicals usage in Tomato (Vegetable) Production in the Offinso-North District - Boateng, Kofi Konadu (2014)
A thesis submitted to the Department of Materials Engineering of the College of Engineering, in partial fulfilment of the requirement for the degree of Master of Science, in Environmental Resources Management